A new species of Machaerota Burmeister (Hemiptera: Cercopoidea: Machaerotidae) from China and Laos - Nie, Jing; Liang, Ai-Ping (Zootaxa, 2008)
A new species of the tube spittlebug genus Machaerota Burmeister (Hemiptera: Cercopoidea: Machaerotidae), M. conicapita sp. nov. (southwestern China: Yunnan; Laos: Borikhane) is described and illustrated. A checklist of Machaerota from China and a key to 12 species are provided.